Turning to the past to see the future: The interpretations of archaic guarani law through the episode of death of fathers Roque Gonzáles, João de Castilhos and Afonso Rodrigues (1628) and their contemporary implications - Lima, Henrique Pereira (Seven Editora, 2023)
In the seventeenth century, the Society of Jesus was already a significant acculturating force in the American colonial process, putting in direct contact, on the one hand, with the Iberian and native universe and, on the other, creating new forms of relationship between natives and Iberians, sometimes conflicting. In this process, the work of the Jesuit priests gave shape to episodes of great impact on the American imaginary, both colonial and contemporary, from which emerge the Amerindians and priests, with different features arising from the different interpretations that are made about these historical subjects. Among the conflicts that marked the American continent throughout the Iberian colonialist project due to its military, religious, cultural, historical, and jurisprudential developments, the one that occurred in 1628, when the priests Roque Gonzáles, João de Castilhos, and Afonso Rodrigues were killed in the region of Caaró/Pirapó, in the northwest of the current State of Rio Grande do Sul. The Indians of that territory, led by the cacique-pajé Ñezú, according to the investigations of investigation and the processes of canonization, offered fierce resistance to the Jesuit action in the defense, according to the same processes, of their social organization, called by the natives the "ancient way of being," which, to the Eurocentric gaze, was nothing more than the expression of barbarism and native paganism. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-031